Hydrological processes at Inle Lake (Southern Shan State, Myanmar) inferred from hydrochemical, mineralogical and isotopic data†. Issue 4 (3rd July 2016) - Thin, Myat Mon; Sacchi, Elisa; Setti, Massimo
ABSTRACT: A one-year hydrochemical and isotopic monitoring was conducted at the Inle Lake, the second largest lake in Myanmar, also considering sediment samples. Lake waters are characterised by low electrical conductivities (236–489 μS/cm), neutral to alkaline pH (7.36–9.26), oxidising Eh (329–457 mV) and Ca–Mg–HCO3 facies. Stable isotopes indicate that lake waters are only slightly affected by evaporation, are fully flushed yearly and are not stratified. Carbonate equilibria dominate the lake water hydrochemistry. In summer, photosynthetic activity and temperature increase induce calcite precipitation, as testified by its high content in the sediments, up to 97 %, and by its isotopic composition. The short residence time and endogenic calcite precipitation likely prevent the accumulation of contaminants and nutrients in lake waters. This study suggests a high resilience of the system to anthropogenic disturbances and demonstrates the sediment potential for the reconstruction of the environmental evolution in time and for the anthropogenic impact assessment.